Analisis Terhadap Kinerja Saham Perusahaan (Studi Kasus PT. Trias Sentosa Tbk. – TRST) - Saputra, Saputra; Supriadi, Yoyon (LPPM Institut Bisnis dan Informatika Kesatuan, 2018)
In this study, the author is interested in choosing the object of PT Trias Sentosa Tbk because the company is engaged in the packaging and plastic sector. These conditions require the company to be able to analyze the financial performance and performance of the company's shares so that the company routinely measures performance, evaluates, compares with the company's targets, discusses the failures faced by the company, communicates the results of the evaluation and plans a performance improvement program for the company's future prospects. will come. The purpose of this study was to analyze the financial performance and performance of the company's shares in 2012 to 2016 at PT Trias Sentosa Tbk. The research process was carried out by using financial statements for five years, namely the period 2012 - 2016. The research methodology used was the research method and analytical method. The research method uses descriptive, quantitative and qualitative methods. Analytical methods using trend analysis of financial ratio analysis and SWOT analysis. Based on the results of this study, it can be concluded that the company's financial performance is still not effective and efficient can be seen from the company's net profit which has decreased. This decrease was caused by an increase in the cost of goods sold and operating expenses. In addition, the ability of management to manage all of the company's assets is still not effective, especially in managing the company's fixed assets so that the condition affects the performance of the company's stock which has decreased in terms of stock prices and Earning Per Share and less optimal improvement in the company's Price Earning Ratio